(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Breast milk is the prime source of nourishment and immunity of the baby. Stanya Kshaya, which appears to be a fairly simple ailment but is really problematic for children’s health, is one of the problems of present era. Lactation insufficiency is 30–40% prevalent in Asian and tropical nations like India. In Ayurveda certain herbs are specifically indicated for increasing breast milk and Acharya Charaka has described Stanya-janana Mahakashaya for it. Few explorations have been conducted regarding above, but no one has covered all aspects comprehensively thus this paper aim to collect and comprehensive review information available regarding concept of Stanya, its Kshaya and role of Stanya-janana Mahakashaya in its management. Methodology: This review is in a narrative format and done from literature and publications relevant to Stanya Kshaya and role of Stanya-janana Mahakashaya. Results: Stanya has been described in detail along with opinion of various Acharyas, Stanya sampata and the reasons for Stanyakshya mentioned then finally role of Stanya-janana Mahakashaya of Acharya Charaka which includes 10 herbs as- Veerana, Shali, Shasthik, Ekshuvalika, Darbha, Kusha, Kaasha, Gundra, Ithkata, Katruna. Drugs in this Kashaya help in increasing quantity of milk. Discussion: Stanya-janana Mahakashaya has active principles which increase quantity of milk, so can be used in Stanya Kshaya and leads to healthy Stanya.